Exploring Emerging Technologies in Online Medical Education: A Survey of Women's Online University - Quraishi, Tamanna; Hakimi, Musawer; Hakimi, Nargis; Khani, Atefeh Mohammad; Zahid, Nabila; Mohammadi, Farida Gul (PT. Riset Press International, 2024)
This study explores the utilization and perceptions of emerging technologies in online medical education, with a focus on instructional tools and methods. The purpose is to assess the current landscape of technology integration, understand faculty and student perceptions, and identify potential applications for enhancing teaching effectiveness and promoting gender inclusivity. A quantitative research design was employed, involving a sample of 120 participants from three faculties: Medical, Pharmacy, and Stomatology. Data were collected through a structured online survey questionnaire, designed to gather information on demographics, technology utilization, teaching effectiveness perceptions, integration challenges, and opinions on gender inclusivity. Descriptive statistics were used to analyze quantitative data, while qualitative data from open-ended questions were analyzed thematically. The results indicate a significant utilization of emerging technologies in online medical education, with mobile learning and gamification being the most promising tools for teaching effectiveness. However, challenges such as technical support and resistance to integration were identified. Despite these challenges, participants generally perceived emerging technologies as effective in enhancing learning experiences, with potential for addressing gender disparities in medical education. In conclusion, the findings underscore the importance of leveraging emerging technologies to enrich online medical education, promote gender inclusivity, and enhance teaching effectiveness. Recommendations include providing adequate technical support and professional development for faculty, addressing resistance to technology integration, and further exploring the potential of emerging technologies in medical education.